(untitled) (Indonesian Journal of Counseling and Development, 2024)
This study investigates the importance of management and supervision in ensuring the quality and success of school counseling programs. Effective management practices involve planning, organizing, and overseeing counseling services to ensure they align with students’ needs and deliver effective, efficient, and high-quality support. Supervision provides counselors with essential guidance, monitors service delivery quality, and promotes professional development through skill improvement and problem-solving. This collaborative approach fosters communication, accountability, and continuous program improvement. Ultimately, strong management and supervision empower counselors to deliver high-quality services that benefit students, parents, and school staff